Use of Silica Fume as Low-Cost Absorbent Material for Nickel Removal from Aqueous Solutions - Kalkan, Ekrem; Nadaroglu, Hayrunnisa; Celebi, Neslihan (Asian Journal of Chemistry, 2014)
The potential of economically low-cost cellulose containing waste materials like silica fume assessed for nickel adsorption from aqueous solutions. In this study, the potential use of silica fume in the remediation of polluted heavy metal water to remove nickel ions is presented. The effects of contact time, initial nickel concentration, pH, temperature, adsorbent dosage on the uptake of nickel were studied in batch process. The experimental investigation results show that activated silica fume has a high level of adsorption capacity for nickel ion. The adsorption data was correlated with the Langmuir and Freundlich isotherm models. It was found that the Langmuir and Freundlich isotherms fitted well to the data. Consequently, it is concluded that nickel is considerably adsorbed on silica fume and silica fume can be successfully used for the removal of the nickel ions from the aqueous solutions with heavy metals.